PENGARUH PENGENDALIAN INTERNAL DAN AUDIT INTERNAL DALAM MENDETEKSI KECURANGAN (FRAUD) - Putri, Rahmita Ariami; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research aims to know the influence of internal controls against fraud levels in PT Graha Envirotama Knights and to know the influence of internal audit towards the level of cheating in PT Graha Envirotama Knights. The technique of sampling by the census method because the samples processed are taken from all members of the population, so that the obtained Samples as many as 32 employees of PT Graha Envirotama Knights who work in the financial section. The dependent variable in this study i.e. the level of cheating, while the independent variable in this study i.e. internal control and internal Audit. Technique of data analysis was done using multiple linear regression were used to examine the influence of variables the dependent variables independent of using program SPSS version 17. Based on the results ofa multiple regression analysis with a level of significance of 5%, then the research indicates that: (1) Internal control effect on the level of cheating and (2) Internal Audit have an effect on the level of Cheating in PT Graha Envirotama Knights.Keywords: Internal control, Internal Audit, the level of cheating